SIFAT FISIS MEKANIS PAPAN PARTIKEL DARI LIMBAH KAYU GERGAJIAN BERDASARKAN UKURAN PARTIKEL - Hamdi, Saibatul (Jurnal Riset Industri Hasil Hutan, 2010)
This research to exploit the waste sawdust of wood lua (Ficus glomerata ROXB) for the making particle board with the variation size measure particle that is 60 mesh, 80 mesh and mixture (60 mesh+80 mesh). Wood lua represent the wood less be recognized and to lower specific gravity. Agglutinant use the glue of Urea Formaldehyda (UF) with the glue concentration 20% from dry weight particle substance. The result of research show the average value board particle wood lua made for moisture content to range from 9,25-9,41%; wood density as 0,60-0,63 gr/cm3; thickness swelling asÂ  9,13-9,53 %; modulus of rupture (MoR) 97,63-101,59 kgf/cm2; modulus of elasticity (MoE) 1,12-1,32.104 kgf/cm2; tensile strength as 2,96-3,99 kgf/ cm2. As a whole result examinationÂ  nature of fisis and mechanical particle board wood lua the standard quality of SNI 03-2105-2006 except for the examination modulus of elasticity (MoE).Key wood : lua, fisis, mechanical, particle.